2010
DOI: 10.1177/1471301210375338
|View full text |Cite
|
Sign up to set email alerts
|

Coping with dementia and older families of adults with Down syndrome

Abstract: The authors studied a group of older carers of aging adults with Down syndrome (DS) to ascertain what effects such caregiving may have on them given the presence or possibility of age-associated decline or dementia. The study also examined the comparative levels of care provided, key signs noted when decline was beginning, the subjective burden experienced, and what were the key associated health factors when carers faced a changed level of care. The authors found that this group was made up of long-term, comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…In 2010, a review found a lack of research focusing on dementia care for people with learning disabilities (Courtenay, Jokinen, & Strydom, ). Since then, there has been some research into components of care, staff knowledge and management strategies and environmental factors for people with learning disabilities and dementia living in group homes and special care units (De Vreese et al., ; Janicki, Zendell, & DeHaven, ; Iacono, Bigby, Carling‐Jenkins, & Torr, ). Initial small‐scale studies of the use of reminiscence therapy, Singing for the Brain sessions and personalised life story books and rummage boxes suggest that these interventions are acceptable to people with learning disabilities and staff and have the potential to lead to positive outcomes such as supporting communication, memory, social engagement, choice, mood and well‐being (Crook, Adams, Shorten, & Langdon, ; Stueber & Hassiotis, ; Ward & Parkes, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2010, a review found a lack of research focusing on dementia care for people with learning disabilities (Courtenay, Jokinen, & Strydom, ). Since then, there has been some research into components of care, staff knowledge and management strategies and environmental factors for people with learning disabilities and dementia living in group homes and special care units (De Vreese et al., ; Janicki, Zendell, & DeHaven, ; Iacono, Bigby, Carling‐Jenkins, & Torr, ). Initial small‐scale studies of the use of reminiscence therapy, Singing for the Brain sessions and personalised life story books and rummage boxes suggest that these interventions are acceptable to people with learning disabilities and staff and have the potential to lead to positive outcomes such as supporting communication, memory, social engagement, choice, mood and well‐being (Crook, Adams, Shorten, & Langdon, ; Stueber & Hassiotis, ; Ward & Parkes, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…dementia, down syndrome, health and social care policy and practice, intellectual disability, learning (intellectual) disabilities, palliative and terminal care, staff training homes and special care units (De Vreese et al, 2012;Janicki, Zendell, & DeHaven, 2010;Iacono, Bigby, Carling-Jenkins, & Torr, 2014). Initial small-scale studies of the use of reminiscence therapy, Singing for the Brain sessions and personalised life story books and rummage boxes suggest that these interventions are acceptable to people with learning disabilities and staff and have the potential to lead to positive outcomes such as supporting communication, memory, social engagement, choice, mood and well-being (Crook, Adams, Shorten, & Langdon, 2016;Stueber & Hassiotis, 2012;Ward & Parkes, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Accounts of the experiences of people with Down syndrome and dementia from their own perspective are extremely limited with research recommending inclusion in further studies to understand this perspective first hand (Hahn, Fox, & Janicki, 2015;Strydom et al, 2009). A wider range of research is available that focuses on the process of screening and diagnosis of dementia in people with intellectual disabilities (Carr & Collins, 2014;O'Caoimh, Clune, & Molloy, 2013;Moriconi, 2015;Nieuwenhuis-Mark, 2009) or on observations from the perspective of family members (Carling-Jenkins, Bigby, & Iacona, 2012;Janicki, Zendell, & DeHaven, 2010) and staff (McCarron, McCallion, Fahey-McCarthy, Connaire, & Dunn-Lane, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing subjective and objective measures of burden, few differences have been found between staff carers in ID service settings and foster family situations (McCallion, Nickle, & McCarron, 2005). Little work exists reporting specifically on caregiving in the family context (an exception is Janicki, Zendell, & DeHaven, in press). What can be gleaned from the broader literature is that families appear to have limited involvement and little input regarding dementia care as it affects their relative (Janicki et al., 2005; Wilkinson, Kerr, Cunningham, & Rae, 2004).…”
Section: Carer Issuesmentioning
confidence: 99%